Context Pruning for More Robust SMT-based Program Verification - Zhou, Yi; Bosamiya, Jay; Li, Jessica; Heule, Marijn; Parno, Bryan (Formal Methods in Computer-Aided Design (FMCAD), 2024)
SMT solvers provide powerful proof automation for program verification. However, relying on SMT solvers also leads to proof instability, where a previously successful proof may fail after the developer makes trivial modifications to the source program. Such instability is a major headache for developers, but the causes and potential mitigations for it have received limited attention. In this study, we find that irrelevant query context accounts for 78% of the instability in existing program-verification query sets. As a result, we design SHAKE, a novel technique that leverages the structure in program-verification SMT queries in order to filter out irrelevant context from such queries. SHAKE is the first SMT-level technique that targets instability, and we implement it as a pre-processing step for SMT solvers. We evaluate SHAKE on real-world, large-scale query sets, and we find that it leads to large reduction in context and a 29% and 41% improvement in query stability on Z3 and cvc5, with minor performance overhead.